2017
DOI: 10.3389/fimmu.2017.01201
|View full text |Cite
|
Sign up to set email alerts
|

CpG-ODN Facilitates Effective Intratracheal Immunization and Recall of Memory against Neoantigen-Expressing Alveolar Cells

Abstract: Intrapulmonary immune reactions are impaired by the tolerogenic environment of the lung. This is manifested by the absence of effective endogenous T cell responses upon neoantigen expression. This tolerance is considered to contribute to lung cancer and inefficient immune therapeutic interventions. To investigate the mechanisms contributing to lung tolerance and to overcome these restrictions, we developed a transgenic mouse model with induction of a neoantigen (OVA) exclusively in alveolar type II epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Therefore, nanoparticles were coloaded with OVA protein and a nucleic acid adjuvant, CpG ODN 1826 (a single-stranded DNA agonist for TLR9). CpG DNA has been shown to enhance the CD8 + T cell response and has precedence for use in pulmonary immunization. ,, CpG was electrostatically complexed to OVA–NP conjugates (Figure S2B), and this formulation is referred to henceforth as OVA–NP/CpG or the “nanoparticle vaccine”.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, nanoparticles were coloaded with OVA protein and a nucleic acid adjuvant, CpG ODN 1826 (a single-stranded DNA agonist for TLR9). CpG DNA has been shown to enhance the CD8 + T cell response and has precedence for use in pulmonary immunization. ,, CpG was electrostatically complexed to OVA–NP conjugates (Figure S2B), and this formulation is referred to henceforth as OVA–NP/CpG or the “nanoparticle vaccine”.…”
Section: Resultsmentioning
confidence: 99%
“…CpG DNA has been shown to enhance the CD8 + T cell response and has precedence for use in pulmonary immunization. 40,44,53 CpG was electrostatically complexed to OVA−NP conjugates (Figure S2B), and this formulation is referred to henceforth as OVA−NP/CpG or the "nanoparticle vaccine".…”
Section: Resultsmentioning
confidence: 99%
“…Among various immunomodulatory functions, the liver has the propensity to prime functional CD8+ T cell immunity (20)(21)(22). We previously introduced a transgenic mouse model in which intracellular Ovalbumin (Ova) expression is activated by Tamoxifen (Tam) inducible CreERT2 recombinase (23,24), which allows for elucidating T cell responses towards Ova antigen in defined tissues (25)(26)(27)(28). Using OvaXCre mice, in which CreERT2 is controlled by the albumin promoter, we documented that the frequency of Ova expressing hepatocytes can be adjusted by Tam titration (23,(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…We previously introduced a transgenic mouse model in which intracellular Ovalbumin (Ova) expression is activated by Tamoxifen (Tam) inducible CreERT2 recombinase (23,24), which allows for elucidating T cell responses towards Ova antigen in defined tissues (25)(26)(27)(28). Using OvaXCre mice, in which CreERT2 is controlled by the albumin promoter, we documented that the frequency of Ova expressing hepatocytes can be adjusted by Tam titration (23,(25)(26)(27). Moreover, we demonstrated that adoptive transfer of Ova-specific CD8+ T cells (OT-1 cells) or Ova-specific CD8+ T cell induction by vaccination eliminates low frequencies of Ova expressing hepatocytes.…”
Section: Introductionmentioning
confidence: 99%